2004
DOI: 10.1055/s-2004-814202
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Endoscopic Features of Rectal Carcinoids

Abstract: Atypical endoscopic appearances of rectal carcinoids are observed more frequently as the size of the tumor increases and a finding of ulceration may have a prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 7 publications
3
65
1
4
Order By: Relevance
“…In a Korean study, rectal NETs were discovered in 67 patients out of a total of 86,918 patients who underwent endoscopy between 1989 and 2002 (0.08%; ref. 15). However, this study included individuals who underwent endoscopy for anything other than screening purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Korean study, rectal NETs were discovered in 67 patients out of a total of 86,918 patients who underwent endoscopy between 1989 and 2002 (0.08%; ref. 15). However, this study included individuals who underwent endoscopy for anything other than screening purposes.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19). The male predominance of rectal NETs appears to be more pronounced in Asian populations (13,15,19). There may be differences in susceptibility to rectal NET development between genders according to ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…They are nodules with a wide base, smooth at the surface, covered by a mucosa of normal appearance, or slightly yellow/white [5][6][7][8][9]. Atypical features (observed in 20%) include: semi-pedunculated shape, reddening of the mucosa, central depression, erosion or ulceration on the surface.…”
Section: Endoscopic Diagnosticsmentioning
confidence: 99%
“…Other reports have stated that the tendency for metastatic spread was associated with tumor size, histopathological differentiation, muscular invasion, and lymphovascular invasion [7,20]. Among these factors, tumor size was a simple and reliable indicator for risk of metastatic involvement, which occurred in 3% of tumors with <10 mm diameter [7,20]. Konishi et al have reported prognosis and risk factors of metastasis in colorectal carcinoids [21].…”
Section: Discussionmentioning
confidence: 97%